WRKY transcription factors in plant defense - Javed, Talha; Gao, San-Ji (Trends in genetics, 2023)
WRKY transcription factors (TFs) are transcriptional regulators in plants and have a conserved WRKY motif and various zinc-finger structures.WRKY TFs may integrate signals of pathogen-associated molecular pattern-triggered immunity and effector-triggered immunity.WRKY genes modulate transcription in plant defense responses against environmental stressors like reactive oxygen species burst, Ca2+ influx, mitogen-activated protein kinase activation, phytohormone production, and epigenetic modification.WRKYs may function as master regulators to balance plant growth and stress response.WRKYs could aid the generation of stress-resilient crops by modern molecular breeding for better crop productivity in the face of climate change. Environmental stressors caused by climate change are fundamental barriers to agricultural sustainability. Enhancing the stress resilience of crops is a key strategy in achieving global food security. Plants perceive adverse environmental conditions and initiate signaling pathways to activate precise responses that contribute to their survival. WRKY transcription factors (TFs) are essential players in several signaling cascades and regulatory networks that have crucial implications for defense responses in plants. This review summarizes advances in research concerning how WRKY TFs mediate various signaling cascades and metabolic adjustments as well as how epigenetic modifications involved in environmental stress responses in plants can modulate WRKYs and/or their downstream genes. Emerging research shows that clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas)-mediated genome editing of WRKYs could be used to improve crop resilience. Environmental stressors caused by climate change are fundamental barriers to agricultural sustainability. Enhancing the stress resilience of crops is a key strategy in achieving global food security. Plants perceive adverse environmental conditions and initiate signaling pathways to activate precise responses that contribute to their survival. WRKY transcription factors (TFs) are essential players in several signaling cascades and regulatory networks that have crucial implications for defense responses in plants. This review summarizes advances in research concerning how WRKY TFs mediate various signaling cascades and metabolic adjustments as well as how epigenetic modifications involved in environmental stress responses in plants can modulate WRKYs and/or their downstream genes. Emerging research shows that clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas)-mediated genome editing of WRKYs could be used to improve crop resilience.